The Minority Aging Research Study: Ongoing Efforts to Obtain Brain Donation in African Americans without Dementia - L. Barnes, Lisa; C. Shah, Raj; T. Aggarwal, Neelum; A. Bennett, David; A. Schneider, Julie (Current Alzheimer Research, 2012)
The Minority Aging Research Study (MARS) is a longitudinal, epidemiologic cohort study of decline in cognitive function and risk of Alzheimer’s disease (AD) in older African Americans, with brain donation after death added as an optional component for those willing to consider organ donation. In this manuscript, we first summarize the study design and methods of MARS. We then provide details of ongoing efforts to achieve neuropathologic data on over 100 African Americans participating in MARS and in three other clinical-pathologic cohort studies at Rush University Medical Center. The results examine strategies for recruiting and consenting African Americans without dementia; 2) efforts to maintain high rates of follow-up participation; 3) strategies for achieving high rates of agreement to brain donation; and 4) the methodology of obtaining rapid brain autopsy at death. The implications of these efforts are discussed.
Keywords: aging